Electrostatic tuning of Kondo effect in a rare-earth-doped wide-band-gap oxide - Li, Yongfeng (2013)
As a long-lived theme in solid-state physics, the Kondo effect reflects the many-body physics involving the short-range Coulomb interactions between itinerant electrons and localized spins in metallic materials. Here we show that the Kondo effect is present in ZnO, a prototypical wide-band-gap oxide, doped with a rare-earth element (Gd). The localized 4f electrons of Gd ions do not produce remanent magnetism, but interact strongly with the host electrons, giving rise to a saturating resistance upturn and negative magnetoresistance at low temperatures. Furthermore, the Kondo temperature and resistance can be electrostatically modulated using electric-double-layer gating with liquid ionic electrolyte. Our experiments provide the experimental evidence of tunable Kondo effect in ZnO, underscoring the magnetic interactions between localized and itinerant electrons and the emergent transport behaviors in such doped wide-band-gap oxides.